An Analysis of the Circular Economy Practices of Pesticide Container Waste in Pakistan - Ali Raza; Syed Asif Ali Naqvi; Muhammad Abuzar Mehdi; Muhammad Usman; Sadia Ali; Ashfaq Ahmad Shah; Bilal Hussain (Recycling, 2022)
Empty pesticide container recycling helps control nonpoint source pollution and provides alternative sources for basic materials. This article investigates end users’ adoption of recycling their pesticide container waste and investigates the determinants influencing their adoption. The study uses an extensive farm survey of 210 farmers from the District Faisalabad of the Province of Punjab (Pakistan). It applies the partial least squares structural equation modeling technique to assess the impact of different elements, such as subjective norms, attitude, perceived behavioral control, intention, and environmental concerns, on end users’ adoption regarding recycling of pesticide empty container waste. The results explain that perceived behavioral control and intention to reuse pesticide container waste positively predict end users’ adoption. Furthermore, adoption is positively impacted by attitude, subjective norms, and environmental concerns via the intention to recycle pesticide container waste. The study urges the need to encourage end users to share responsibility for pesticide container waste management for a sustainable society.